Analisis Semantik Leksikal Terhadap Nama Kota Dan Kecamatan Di Daerah Tasikmalaya - Abdul Djabar Zakaria; Rizka Maulidania; Zubaedah Mahdiyah; Silviyuni Meliawati; Aveny Septi Astriani (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
Every place in the world has a name given to give it an identity and make it known. With this basis, the researcher focuses on the names of sub-districts and cities in the Tasikmalaya City and Regency area, including the name Tasikmalaya itself which will be studied using lexical semantic theory. The research method applied is descriptive qualitative. Based on the results of the analysis above, there are several regional names of cities and districts in Tasikmalaya which have interesting origins based on the meaning of regional naming which has lexical meaning, including the areas Tasikmalaya, Singaparna, Manonjaya, Parung Ponteng, Jamanis, Rajapolah, Mangunreja, Mangkubumi, Cibalong and Indihiang. Of the ten regional names that have been explained, each regional name has a history and meaning, a combination of lexemes in the process of naming the region so that this becomes a distinctive feature for people who do not know about it. It can be concluded that the naming of regions in Tasikmalaya originates from the uniqueness and characteristics of naming according to the origins that describe a place or an event in the area concerned.